1991
DOI: 10.1523/jneurosci.11-11-03456.1991
|View full text |Cite
|
Sign up to set email alerts
|

The monaural nuclei of the lateral lemniscus in an echolocating bat: parallel pathways for analyzing temporal features of sound

Abstract: In echolocating bats, three cell groups in the lateral lemniscus are conspicuous for their large size and high degree of differentiation. These cell groups are the intermediate nucleus (INLL), columnar nucleus (VNLLc), and multipolar cell area (VNLLm). All receive projections from the contralateral cochlear nucleus. Previous anatomical studies suggest the hypothesis that these nuclei are important for analyzing the temporal structure of sound. To investigate this possibility, we recorded responses of single un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
206
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(227 citation statements)
references
References 34 publications
20
206
1
Order By: Relevance
“…However, it has been shown that tonotopic organization of monaural nuclei of the lateral lemniscus in big brown bat ( Epitesicus fuscus ) is complicated (Covey & Casseday, 1991), and it is difficult to conclude about the tonotopic organization in the NLL of Japanese house bat. Finer injection with best frequency identification is necessary to solve the issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that tonotopic organization of monaural nuclei of the lateral lemniscus in big brown bat ( Epitesicus fuscus ) is complicated (Covey & Casseday, 1991), and it is difficult to conclude about the tonotopic organization in the NLL of Japanese house bat. Finer injection with best frequency identification is necessary to solve the issue.…”
Section: Discussionmentioning
confidence: 99%
“…To analyze the echoes and pulses themselves, auditory nuclei of bats are remarkably hypertrophied (Zook & Casseday, 1982a), and show specialization related to echolocation (Covey & Casseday, 1995), which is obvious in the medial superior olive (MSO) of the superior olivary complex (SOC) (Casseday, Covey, & Vater, 1988; Covey, Vater, & Casseday, 1991; Grothe, Park, & Schuller, 1997; Grothe, Schweizer, Pollak, Schuller, & Rosemann, 1994) and monaural nuclei of the lateral lemniscus, namely intermediate nucleus (ILL) and compact and multipolar cell divisions of ventral nucleus (VLLc and VLLm) (Covey & Casseday, 1991). Lower brainstem nuclei, namely, cochlear nuclei (CN), SOC, and nuclei of the lateral lemniscus (NLL), analyze specific features of sound and send the analyzed information to the inferior colliculus (IC), which is the largest nuclei in entire subcortical auditory system (Ito, Bishop, & Oliver, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Along the same line, neurons of the octopus cell area diverge on several VNLL neurons (Covey and Casseday, 1986;Vater and Feng, 1990;Adams, 1997;Schofield and Cant, 1997). Finally, neurons in the VNLL appear to inherit physiological properties from neurons in the octopus cell area as both are broadly tuned and preferentially spike to sound onsets (Godfrey et al, 1975;Rhode et al, 1983;Covey and Casseday, 1991;Smith et al, 2005;Zhang and Kelly, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MNTB neurons also project to the VNLL, where they terminate in calyceal-like endings (Adams and Wenthold, 1987). VNLL is part of a monaural ascending system purported to play a role in temporal processing of signals (Covey and Casseday, 1991).…”
Section: Introductionmentioning
confidence: 99%